EXPERIENCE IN THE USE OF MINIMALLY INVASIVE OPERATIONS IN ACUTE APPENDICITIS - Игорь Григорьевич Мугатасимов; Андрей Михайлович Алексеев; Кристина Валерьевна Валиахмедова; Андрей Александрович Берсенев; Сергей Сергеевич Чернявский (Медицина в Кузбассе)
The study included 1520 patients with acute appendicitis who were treated in two large surgical hospitals in Novokuznetsk from 2010 to 2014 inclusive, as well as from June 2016 to June 2018.